2005
DOI: 10.2337/diabetes.54.6.1698
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 4,5-Bisphosphate Reverses Endothelin-1–Induced Insulin Resistance via an Actin-Dependent Mechanism

Abstract: Phosphatidylinositol (PI) 4,5-bisphosphate (PIP2) plays a pivotal role in insulin-stimulated glucose transport as an important precursor to PI 3,4,5-trisphosphate (PIP3) and a key regulator of actin polymerization. Since endothelin (ET)-1 impairs insulin sensitivity and PIP2 is a target of ET-1–induced signaling, we tested whether a change in insulin-stimulated PIP3 generation and signaling, PIP2-regulated actin polymerization, or a combination of both accounted for ET-1–induced insulin resistance. Concomitant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 52 publications
3
39
0
Order By: Relevance
“…In vascular smooth muscle cells and adipocytes, ET-1 causes insulin resistance by a PKCdependent mechanism (14,17). Endothelin has also been found to impair insulin action through interactions with downstream signaling events at the plasma membrane involving PIP 2 and actin cytoskeleton components of the insulin response (18), suggesting that ET-1 negatively impacts cytoskeletal structure important for insulin function. From this perspective, the question of effects of endothelin antagonism on glucose extraction as distinct from effects on blood flow is of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vascular smooth muscle cells and adipocytes, ET-1 causes insulin resistance by a PKCdependent mechanism (14,17). Endothelin has also been found to impair insulin action through interactions with downstream signaling events at the plasma membrane involving PIP 2 and actin cytoskeleton components of the insulin response (18), suggesting that ET-1 negatively impacts cytoskeletal structure important for insulin function. From this perspective, the question of effects of endothelin antagonism on glucose extraction as distinct from effects on blood flow is of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, sustained exposure of insulin-responsive cells to endothelin 1 (ET-1) induces insulin resistance (14 -16). Molecular studies have shown that this effect is mediated by effects of endothelin on a number of components of the insulin signaling cascade, including heterologous desensitization of insulin signaling by a G ␣q/11 -mediated pathway (14), impaired stimulation of phosphoinositol-3 kinase by insulin receptor substrate (IRS)-1 and IRS-2 (14,17), and impairments in downstream plasma membrane phosphatidylinositol 4,5-bisphosphate (PIP 2 ) and actin cytoskeleton interactions (18).…”
mentioning
confidence: 99%
“…Furthermore, a very recent study demonstrated that chronic ET-1 treatment, which causes insulin resistance, results in dysregulation of cortical F-actin by diminishing the plasma membrane PI(4,5)P 2 level. Importantly, exogenous replenishment of PI(4,5)P 2 , but not PI(3,4,5)P 3 , restores the disrupted cortical F-actin structure and subsequently reverses the insulin resistance induced by chronic ET-1 treatment [226]. Thus, PI(4,5)P 2 and its dynamic turnover in response to extracellular stimuli including insulin are physiologically critical for maintaining proper membrane trafficking and actin dynamics, thereby directly affecting insulin-induced redistribution of GLUT4 .…”
Section: (4) Actin Dynamics Are Regulated By Both Phosphoinositimentioning
confidence: 99%
“…Recently, several studies have also demonstrated the importance of proper PI(4,5)P 2 metabolism in the regulation of GLUT4 recycling and its insulin responsiveness [194,[223][224][225][226]. The major pathway for PI(4,5)P 2 production is via sequential phosphorylation of PI by a PI 4-kinase to generate PI(4)P followed by phosphorylation with type I PIP 5-kinase.…”
Section: (4) Actin Dynamics Are Regulated By Both Phosphoinositimentioning
confidence: 99%
“…153 This same mechanism may also be operative in metabolic tissues, inasmuch as ET-1 impairs insulinstimulated translocation of GLUT4 in adipocytes. 154,155 …”
Section: Pathophysiological Cross-talk Between Metabolic and Vascularmentioning
confidence: 99%